Tower tank valve flushing system for dairy facilities - Joseph P. Harner; James P. Murphy; John F. Smith (Kansas Agricultural Experiment Station Research Reports, 1998)
Flushing characteristics of a tower tank valve flushing system with a 12-inch-diameter manual valve were determined. Data were obtained using the outside cow alleys in a fourrow freestall barn. The alleys were 12 ft wide and 420 ft long with a 2% slope. The average flow rate exceeded 8,000 gallons per minute (gpm) when the average head was above 30 ft and the manual valve opened 80 degrees. Opening the valve to 90 degrees increased the flow rate to over 9,700 gpm. The velocity of the flushing wave was 8.5 fpm with a flow depth of 3.5 in. The estimated wave duration or alley contact time was 14.6 sec with a 25-40 sec release time from the flush tank. The flow rate ranged from 5,300 gpm to 7,200 gpm when the average head was between 16 and 28 ft.; Dairy Day, 1998, Kansas State University, Manhattan, KS, 1998;
Keywords: Dairy Day; 1998; Kansas Agricultural Experiment Station contribution; no. 99-158-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 821; Flushing; Manure; Water usage; Freestall